"One injustice can never become a legitimate reason to commit another": Condorcet, women's political rights, and social reform during the French Revolution (1789–1795). Issue 2 (3rd April 2023) - Ansart, Guillaume
ABSTRACT: Writing around the time of the French Revolution, Condorcet was a very early advocate of women's suffrage. To fully appreciate the importance and originality of his contribution to the cause of women's political rights, it is necessary to situate his ideas within the broad context of revolutionary feminist activism in general, its goals, modes of expression, successes or failures, as well as the nature of the opposition it faced. Such contextualization confirms that Condorcet, whose affirmation of women's voting rights was grounded in the theory of natural rights, was the most articulate and consistent feminist voice during the Revolution. My analysis of the Convention's decision to ban all women's political clubs in the fall of 1793 also calls into question a common and influential assessment of the Revolution. In contrast to the anti-feminist arguments of the Montagnards who wielded power at the time, arguments predicated on a restrictive understanding of natural law, Condorcet's earlier feminist reasoning based on natural rights, one of the central political concepts of the Enlightenment, casts doubt on the claim that the Revolution was inherently misogynist and that the bourgeois public sphere to which it gave rise was founded on the exclusion of women.